2008
DOI: 10.1161/circinterventions.108.797928
|View full text |Cite
|
Sign up to set email alerts
|

Interference of Drug-Eluting Stents With Endothelium-Dependent Coronary Vasomotion

Abstract: Background-There is evidence that endothelial coverage of drug-eluting stents might be delayed or absent, a risk factor for late thrombotic events. We studied the effects of different drug-polymer-device iterations on endothelium-dependent coronary vasomotion. Systemic markers of endothelial inflammation were correlated with coronary vasomotor changes. Methods and Results-Patients with paclitaxel-eluting stents (nϭ11), sirolimus-eluting stents (nϭ21), biolimus A9-eluting stents (nϭ28), zotarolimus-eluting sten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 30 publications
2
54
1
4
Order By: Relevance
“…However, exercise and pacinginduced vasoconstriction was observed at the edges of DES and segments distal to DES. 286, 287 It has been reported that vasoconstriction in segments adjacent to stents in response to intracoronary acetylcholine infusion is more severe in DEStreated vessels than in BMS-treated vessels. 288,289 Recent studies in a porcine model and in patients with coronary artery disease have suggested that Rho-kinase, a molecular switch that regulates vascular smooth muscle contraction, plays an important role in the pathogenesis of coronary dysfunction after DES implantation, and that DES induces smooth muscle dysfunction as well as endothelial dysfunction.…”
Section: Coronary Spasm After Pcimentioning
confidence: 99%
“…However, exercise and pacinginduced vasoconstriction was observed at the edges of DES and segments distal to DES. 286, 287 It has been reported that vasoconstriction in segments adjacent to stents in response to intracoronary acetylcholine infusion is more severe in DEStreated vessels than in BMS-treated vessels. 288,289 Recent studies in a porcine model and in patients with coronary artery disease have suggested that Rho-kinase, a molecular switch that regulates vascular smooth muscle contraction, plays an important role in the pathogenesis of coronary dysfunction after DES implantation, and that DES induces smooth muscle dysfunction as well as endothelial dysfunction.…”
Section: Coronary Spasm After Pcimentioning
confidence: 99%
“…Their study revealed that SES and PES showed vasoconstriction, while on the other hand, ZES and BES had vasodilatory responses that were similar to BMS (Hamilos et al, 2008b).…”
Section: Zotarolimus-eluting Stents (Zes Endeavormentioning
confidence: 97%
“…Comparison of first generation and second generation DES: Hamilos et al (2008b) evaluated the influence of BMS and four types of DES on endothelium-dependent vasodilation. Their study revealed that SES and PES showed vasoconstriction, while on the other hand, ZES and BES had vasodilatory responses that were similar to BMS (Hamilos et al, 2008b).…”
Section: Zotarolimus-eluting Stents (Zes Endeavormentioning
confidence: 99%
“…38 The recent studies demonstrated that coronary vasomotion was preserved with a new-generation biolimus-eluting stent with bioresorbable polymers as compared with the Cypher stent. 39, 40 Since we are examining the Rho-kinase activation with a new generation of DES, we would like to report our findings separately in the future. However, it also should be emphasized that Cypher TM has already been deployed in millions of patients worldwide, and thus, aggressive efforts should be made to improve coronary vasomotion in those patients implanted with Cypher TM .…”
Section: Clinical Implications Of the Studymentioning
confidence: 99%